Peningkatan Penguatan Pemahaman Kader Penggerak Trimulyo Genuk Mengenai Perlindungan Hukum Bagi Perempuan - Surayda, Helen Intania; Yulistyowati, Efi; Nuryanto, Ahmad Dwi (Fakultas Hukum Universitas Semarang, 2024)
Women are considered second-class citizens who often receive stereotyped views and attitudes or negative labels, as well as acts of violence, both in the form of control even with the intention of protection, which eliminates physical and mental integrity, resulting in the loss of equality, enjoyment and basic freedoms as human beings. Indonesia, as a developing country, has a bad reputation in terms of human rights violations, one of which is that these violations can be classified as acts of violence against women. The core of legal protection for women in the UDHR respects the humanity of every person because they are born as human beings. The presence of the PKDRT Law, the TPKS Law which regulates the right to restitution and assistance funds, and Perma Number 1 of 2024 concerning Guidelines for Adjudicating Criminal Cases Based on Restorative Justice. provide confidence to the community to dare to report their cases. The driving cadres are the leading partners who are directly involved in community issues. Based on this, the problem in this Community Service (PKM) activity can be formulated as the lack of understanding of the Trimluyo Genuk driving cadres regarding legal protection for women. This PKM activity was carried out using lecture, discussion and question and answer methods. In this PKM activity, Trimulyo's cadres gained information developments and strengthened their understanding of legal protection, as indicated by an increase in the average general understanding of 13 participants of 81.54%.